Kajian Literatur Tentang Permainan Tradisional pada Anak Usia Dini - Mita Sari; Salwa Afrilla Patilima; Isnawati Daintaw; Dela Septia Hungopa; Juwita Moodumbi; Srimulyani Srimulyani (STIKes Ibnu Sina Ajibarang, 2025)
The development of the era has influenced children's play patterns, who are now more familiar with digital games than traditional games. In fact, traditional games have educational and cultural values ​​that are important for the development of children's gross motor skills and psychomotor skills. This study uses a literature study method by analyzing 15 relevant articles to examine the contribution of traditional games to early childhood development. The results of the study show that traditional games such as catapults, jump rope, and gobak sodor can improve children's coordination, balance, and social skills through interaction and cooperation. This game not only strengthens large muscles, but also shapes children's character holistically, including empathy, responsibility, and decision making. Therefore, it is important for parents and educators to preserve and integrate traditional games in learning activities as a means of stimulating children's overall development.